THU0051 OFF-LICENCE USE OF ANAKINRA IN CRITICALLY ILL ADULTS WITH SUSPECTED HAEMOPHAGOCYTOSIS – A SINGLE CENTRE EXPERIENCE. (June 2019) - Shabbir, Shabnam; Al-Abdulla, Ahmad; Kinderlerer, Anne; Sohal, Mamta; Layton, Mark; Hill, Peter; Corbett, Richard; Lightstone, Liz; Cairns, Tom; Mason, Justin; Cooper, Nichola; Youngstein, Taryn
Abstract : Background: Anakinra is a recombinant interleukin-1 receptor antagonist licensed in Europe for the treatment of rheumatoid arthritis, periodic fever and auto-inflammatory syndromes 1 . It is increasingly recognised as an adjunct in the treatment of macrophage activation syndrome/secondary haemophagocytic lymphohistiocytosis (HLH) 2 . Objectives: To analyse the indication, patient demographic and outcomes of critically unwell patients receiving anakinra for suspected HLH. Methods: Retrospective cohort analysis of adult patients who received anakinra over a 12-month period at Imperial College Healthcare NHS Trust, London. Results: Eleven patients received anakinra (both sub-cutaneous and intravenous, dose range 100– 460 mg daily), ten alongside conventional treatments for HLH. 64% were male. Median age at presentation was 32 years (range 27-73 years). Serum ferritin was significantly elevated (median 17371 (range 4335 – 160, 664 micrograms per litre) in all cases. Ten of eleven cases underwent bone marrow examination which showed haemophagocytosis in all cases. Underlying diagnoses were: T-cell Lymphoma (n=3), Mantle Cell Lymphoma (n=1), gastric MALT Lymphoma (n=1), infection (n =3: Group A streptococcus in a patient with inflammatory arthritis (bone marrow not performed), EBV and CMV), retained products of conception (n=1), post-transplant-related lymphoproliferative disorder in a case of systemic lupus with renal transplant (n=1), unknown (n=1). Overall mortality was 55%. The underlying diagnosis were: T –cell Lymphoma (n=3), gastric MALT Lymphoma (n=1), CMV infection in a post-renal transplant immunosuppressed patient (n=1, sarcoidosis underlying diagnosis), unknown (n=1). 100% of cases with T-cell lymphoma as the cause of HLH died, despite two of the three receiving standard chemotherapy to treat the lymphoma. The third case was diagnosed with non-hepatosplenic gamma delta T-cell lymphoma post-mortem. In the five cases that survived, anakinra led to rapid recovery in three cases (underlying diagnoses: Mantle Cell lymphoma (managed entirely steroid free), HLH secondary to retained products of conception, and inflammatory arthritis with Group A Streptococcal pneumonia). The two remaining cases had underlying PTLV and EBV-driven HLH. Anakinra led to rapid resolution of fever, improvement in respiration and dramatic decreases in serum ferritin (up to 98% reduction in three weeks). There were no identifiable complications from anakinra use. One case remains on anakinra, a young male with inflammatory arthritis and Group A Streptococcus pneumonia, who rapidly flared again two days after cessation with full recovery once anakinra was re-instigated. Conclusion: Anakinra can be a useful adjunct in the treatment of suspected HLH but appears to be less efficacious in those with underlying haematological malignancy, where mortality remains high. In critically ill patients we have used it intravenously, and in higher doses, where the half-life is shorter and twice daily dosing is required. Anakinra was well tolerated and its short half-life makes it ideal for use in suspected sepsis-driven HLH. One case was managed entirely steroid-free using anakinra. This allowed for the identification of an underlying lymphoma which may have missed had high-dose steroids been used. Larger studies will help us ascertain whether earlier anakinra use may spare steroid and chemotherapy side-effects and improve patient outcomes. References: [1] Clinical Commissioning Policy: NHS England Reference: 170062P. 2018. [2] Grom AA, et al. Nat Rev Rheumatol. 2016; 12(5): 259–268. Disclosure of Interests: Shabnam Shabbir: None declared, Ahmad Al-Abdulla: None declared, Anne Kinderlerer: None declared, Mamta Sohal: None declared, Mark Layton: None declared, Peter Hill: None declared, Richard Corbett: None declared, Liz Lightstone: None declared, Tom Cairns : None declared, Justin Mason Consultant for: Prof Mason has worked as a paid Consultant for Roche/Chugai and Novartis, Speakers bureau: Prof Mason has been a paid speaker for Roche/Chugai, Nichola Cooper: None declared, Taryn Youngstein: None declared